The role of families in the response of inclusive schools: A case study from teacher’s perspectives - Corres-Medrano, Irune; Santamaría-Goicuria, Imanol; Fernandez-Villanueva, Itziar; Smith-Etxeberria, Klara (Frontiers in Education, 2022)
Some families identified as being at risk, including families of immigrant origin, demonstrate a lower degree of participation in school communities. This constitutes a major challenge for educational institutions. In this research, a case study including three public schools affected by school segregation was carried out. The aim was to analyze and disseminate teachers’ experiences and contributions around the question of family-school relationships, particularly measures they take to promote the participation of families in the daily life of schools. This included a particular focus on schools characterized by high degree of segregation and pupils with higher levels of social vulnerability. The study was carried out as a multi-local ethnographic project in three schools in the Basque Country, Spain, through participant observation, interviews, and focus groups with teachers, pupils, school leadership teams and psycho-pedagogical teams. The results obtained show that schools condition the participation of families, especially those most at risk, and that this has an impact on the socio-emotional development of children. They also highlight the importance of building communication and relationship channels between families and schools. In the current age of globalization, the need to create a network of collaborative and trusting relationships between families and teachers is more evident than ever. Only by these means can children be properly supported to achieve their maximum potential.